Relational Communication : an Interactional Perspective To the Study of Process and Form. - Rogers, L. Edna (LEA's series on personal relationships., 2003)
This text brings together a full treatment of the relational communication perspective on the study of relationships. This perspective takes to heart the formative nature of communication by focusing on the codefined patterns of interaction by which members jointly create their relationship.